Effect of Ranirestat on Sensory and Motor Nerve Function in Japanese Patients with Diabetic Polyneuropathy: A Randomized Double-Blind Placebo-Controlled Study - Jo Satoh; Nobuo Kohara; Kenji Sekiguchi; Yasuyuki Yamaguchi (Journal of Diabetes Research)
We conducted a 26-week oral-administration study of ranirestat (an aldose reductase inhibitor) at a once-daily dose of 20 mg to evaluate its efficacy and safety in Japanese patients with diabetic polyneuropathy (DPN). The primary endpoint was summed change in sensory nerve conduction velocity (NCV) for the bilateral sural and proximal median sensory nerves. The sensory NCV was significantly (P=0.006) improved by ranirestat. On clinical symptoms evaluated with the use of modified Toronto Clinical Neuropathy Score (mTCNS), obvious efficacy was not found in total score. However, improvement in the sensory test domain of the mTCNS was significant (P=0.037) in a subgroup of patients diagnosed with neuropathy according to the TCNS severity classification. No clinically significant effects on safety parameters including hepatic and renal functions were observed. Our results indicate that ranirestat is effective on DPN (Japic CTI-121994).